The Concept of Sakinah as a Normative-Theological Foundation for Gender Equality in Islamic Family Law - Al-kautsar, Azam Mabrury (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
The concept of sakinah in Islam is normatively understood as the ultimate objective of marriage, characterized by tranquility, affection, and compassion, as emphasized in the Qur’an, Surah al-R?m (30:21). Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI) also affirm that the ideal family is one founded upon sakinah, mawaddah, and rahmah. Nevertheless, social realities reveal a considerable gap between these normative ideals and actual practices in society, where patriarchal culture continues to dominate and often places marital relations in unequal positions. Previous studies have largely focused on the normative dimension or state regulation concerning the notion of a sakinah family, but relatively few have specifically linked it to the issue of gender equality. This study seeks to re-examine the concept of sakinah as a foundation for fostering gender equality within the family. Employing a qualitative method based on library research, it draws upon Qur’anic verses, Prophetic traditions, exegetical literature, Indonesian family law regulations, and the works of contemporary scholars. The analysis applies content analysis and discourse analysis to uncover both the normative meaning of sakinah and the embedded gender narratives within interpretations and legal regulations. The findings suggest that sakinah should not be understood merely as a state of harmony, but rather as a relational construct grounded in reciprocity and equality between husband and wife. This underscores the potential of sakinah as a normative framework for building families that are just and egalitarian. The contribution of this research lies in offering a new perspective for the development of Islamic family law that is more responsive to the principles of gender justice and attuned to the dynamics of contemporary Muslim societies. [Konsep sakinah dalam Islam secara normatif dipahami sebagai tujuan utama perkawinan yang menghadirkan ketenteraman, cinta, dan kasih sayang, sebagaimana ditegaskan dalam Al-Qur’an surah Ar-R?m ayat 21. Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan serta Kompilasi Hukum Islam (KHI) juga menegaskan bahwa keluarga ideal adalah keluarga yang sakinah, mawaddah, dan rahmah. Namun, realitas sosial memperlihatkan adanya kesenjangan antara idealitas normatif dengan praktik di masyarakat, di mana budaya patriarkal masih mendominasi dan menempatkan relasi suami-istri dalam posisi yang tidak setara. Kajian sebelumnya umumnya menitikberatkan pada aspek normatif atau regulasi negara mengenai keluarga sakinah, tetapi belum banyak yang secara khusus mengaitkannya dengan isu kesetaraan gender. Penelitian ini bertujuan menelaah kembali konsep sakinah sebagai landasan bagi terciptanya kesetaraan gender dalam keluarga. Dengan menggunakan metode kualitatif berbasis studi pustaka (library research), penelitian ini menghimpun data dari ayat-ayat Al-Qur’an, hadis, literatur tafsir, regulasi hukum keluarga di Indonesia, serta pemikiran ulama kontemporer. Analisis dilakukan melalui pendekatan analisis isi dan analisis wacana untuk menyingkap makna normatif sakinah sekaligus menguraikan narasi gender yang termuat dalam penafsiran maupun regulasi. Hasil penelitian menunjukkan bahwa sakinah tidak semata-mata dimaknai sebagai kondisi harmonis, melainkan juga sebagai konstruksi relasi yang berlandaskan kesalingan dan kesetaraan antara suami dan istri. Temuan ini menegaskan bahwa konsep sakinah memiliki potensi besar sebagai kerangka normatif dalam membangun keluarga yang adil dan egaliter. Kontribusi penelitian ini terletak pada penyajian perspektif baru bagi pengembangan hukum keluarga Islam yang lebih responsif terhadap nilai-nilai keadilan gender serta relevan dengan dinamika masyarakat muslim kontemporer.]